Effect of Exercise Prescription Implementation Rate on Cardiovascular Events - Zhu, Li-Yue; Li, Min-Yan; Li, Kun-Hui; Yang, Xiao; Yang, Yi-Yong; Zhao, Xiao-Xia; Yan, Ting; Li, Meng-Meng; Luo, Si-Qi; Zhang, Mu-Lan; Su, Jin-Zi (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background: In patients with cardiovascular diseases (CVDs) and high risk of CVDs, exercise prescription of cardiac rehabilitation (CR) has become vital. However, the relation between the implementation rate of exercise prescription and cardiovascular events (CVEs) is unclear. Design and Methods: Using administration data from the Rehabilitation Center in a hospital, retrospective analyses of patients aged ≥18 years with CVDs were consecutively enrolled from November 2018 to May 2021. Patients were divided into the high execution group (HEG) and low execution group (LEG) depending on whether completing more than half times of the exercise prescriptions. Baseline characteristics, ultrasonic cardiogram, cardiopulmonary exercise test, follow-up data, and CVEs were collected. Results: The 197 CR patients had a mean age of 61.8 ± 13.7 years and a mean follow-up of 14.8 ± 7.4 months. Among them, 15 patients suffered CVEs, 4 in HEG and 11 in LEG. Incidence of CVEs using chi-square test proved statistically significant difference between the HEG and LEG. Free-event survival analysis using Kaplan–Meier survival plots showed that patients in LEG had poor survival. Cox proportional hazards regression analysis revealed that prescription implementation rate was found to be an independent predictor of CVEs. Conclusions: Our study suggested a significant effect of exercise prescription execution rate on the occurrence of CVEs. And it can be predicted that the HEG of exercise prescription was associated with lower CVDs.